(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
A reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated to simultaneously determine curcumin and desonide in both bulk and pharmaceutical dosage forms. This method is characterized by its simplicity, sensitivity, speed, specificity, precision, and accuracy. The mobile phase consisted of a mixture with a ratio of 65:35 v/v, and the flow rate was maintained at 0.8 mL/min. Chromatographic separation was achieved using a C18 column (250 × 4.6 mm – 5 μm p.s), with ultraviolet detection performed at 240 nm. An injection volume of 20 μL was used. The retention times for desonide and curcumin were 3.45 and 7.51 min, respectively, resulting in distinct and well-defined chromatographic peaks. The respective percentage recoveries were 99.56% and 99.87%. The suggested approach demonstrated strong linearity, accuracy, and precision, and it was effectively used to determine the medicines in pharmaceutical dosage forms. The current approach was created and successfully used to ascertain the quantities of curcumin and desonide in a combined formulation after it was statistically validated in compliance with the ICH recommendations.